Sequence Diversity of Flagellin (fliC) Alleles in Pathogenic Escherichia coli - Reid, Sean D. (American Society for Microbiology, 1999)
To study the molecular evolution of flagellin, the protein subunit specifying flagellar (H) antigens, the fliC genes from 15 pathogenic strains of Escherichia coli were amplified by PCR and sequenced. Comparison of fliC sequences of H6 and H7 strains revealed that alleles have a mosaic structure indicating the occurrence of past horizontal transfer of DNA segments between strains. The close similarity of H7 sequences also indicates the exchange of an entire fliC H7 allele between distant clonal lineages. In addition, the ratio of silent substitutions to amino acid replacements suggests that a short segment in the central region of fliC has been under positive selection in the divergence of H6 and H7 alleles. Phylogenetic analysis demonstrates that the fliC sequences of O157:H7 and O55:H7 serotypes are nearly identical and highly divergent from those of E. coli strains expressing H6 and H2 flagellar antigens. A nonmotile clone of sorbitol-fermenting O157 has rapidly accumulated multiple mutations in fliC, presumably as a result of the silencing of flagellin expression.